Luxembourg : 2011 Article IV Consultation; Staff Report; Informational Annex; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Luxembourg. (IMF Staff Country Reports; Country Report ;, 2011)
An externally driven economic recovery has continued gathering strength in 2010 in Luxembourg. Executive Directors welcomed this development and the authorities' supportive fiscal policy in 2010 as well as their role in stabilizing the financial sector. According to the Financial Sector Assessment Program (FSAP), banks remain exposed to liquidity and credit risks related to intragroup exposures and sovereign bond holdings. Directors welcomed the FSAP update and the authorities' intention to strengthen the regulatory and supervisory frameworks. Directors suggested to revamp the deposit guarantee scheme and supported the target of a balanced budget by 2014.